Peranan Orientasi Pasar dalam Meningkatkan Keunggulan Bersaing pada UMKM Lampu Gentur Cianjur - Yakin, Adam Hakul; Suhaeni, Tintin (Jurnal Riset Bisnis dan Investasi, 2020)
Lampu Gentur is one of the superior products of UMKM Cianjur Regency with poor development and experiencing problems in the decrease in production and a decrease in turnover. The incapability of Lampu Gentur in fulfilling consumer desires and luster move in winning the market. The purpose of this research is to find out how the implementation of market orientation conducted by Lampu Gentur, how competitive advantage made by SME in Cianjur, and how the influence of the market orientation to competitive advantage. This study used a sample of 109 MSMEs. The method used simple linear regression. The result of analysis yielded the formula Y = 21,916+ 0,503x with R square equal to 0,344 which means market orientation able to improve the competitiveness of SMEs Gentur Lamp with value 34,4%.